Investigação dos efeitos do peptídeo liberador de gastrina (GRP) e seu antagonista RC-3095 em células mieloides - Czepielewski, Rafael Sanguinetti (2016)
Tumor microenvironment and inflammatory diseases promote alterations in our immune system along with their development. Several molecules are implicated in this modulation and are therefore considered therapeutic targets. Gastrin-releasing peptide (GRP) is produced in tumors where it promotes cellular proliferation. It is also correlated with chronic diseases, as in rheumatoid arthritis and asthma, and in the acute condition of sepsis. Recently, our group found a direct GRP action over neutrophils, promoting migration. This work aimed to study the interface between GRP-producing tumors and the recruitment of immune cells, as well as extend the cellular studies about neutrophil activation and migration processes promoted by the peptide. In tumors, we observed that a lung adenocarcinoma cell line does not proliferate in response to GRP. Yet, it is induced to migrate when exposed to the peptide, indicating a potential role for GRP in metastasis of this type of cancer. In our tumor immunology studies, we established a novel in vivo model by overexpressing GRP in a melanoma cell line (B16F10). We observed the augment of infiltrating inflammatory monocytes in the tumor microenvironment of these tumors. In parallel, we verified that reactive oxygen species production and migration in response to GRP is dependent of the NADPH oxidase complex. GRP stimulation promotes an intense activation, which culminates in neutrophil extracellular traps (NETs) release. In addition, the GRP receptor (GRPR) antagonist RC-3095 presented anti-inflammatory potential, inhibiting neutrophil migration towards IL-8 and reducing the extent of acetaminophen-induced liver damage. This effect was due to motility alterations in infiltrating neutrophils within the tissue and reduction of cell adhesion molecules. The results presented herein demonstrate the wide panorama of GRP’s interactions in tumor and immune biology.